2023
DOI: 10.1111/acel.13895
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of class I histone deacetylases ameliorates ER‐mitochondria cross‐talk in Alzheimer's disease

Abstract: Several molecular mechanisms have been described in Alzheimer's disease (AD), including repressed gene transcription and mitochondrial and endoplasmic reticulum (ER) dysfunction. In this study, we evaluate the potential efficacy of transcriptional modifications exerted by inhibition or knockdown of class I histone deacetylases (HDACs) in ameliorating ER‐mitochondria cross‐talk in AD models. Data show increased HDAC3 protein levels and decreased acetyl‐H3 in AD human cortex, and increased HDAC2‐3 in MCI periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…111 Additionally, while there is evidence of increased MAP kinase signaling in ALS patients as well as in animal and iPSC models, 57,[112][113][114][115] two compounds identified here were MAP kinase inhibitors (XMD-892, XMD-885). Finally, XMD-892 116 and other compounds (tacedinaline, [117][118][119] MLN4924, 120 piperlongumine, 121,122 prunetin 123 ) have also been under investigation for their antioxidant, anti-inflammatory, anti-ischemic, neuroprotective, and/or antitumour properties.…”
Section: Discussionmentioning
confidence: 99%
“…111 Additionally, while there is evidence of increased MAP kinase signaling in ALS patients as well as in animal and iPSC models, 57,[112][113][114][115] two compounds identified here were MAP kinase inhibitors (XMD-892, XMD-885). Finally, XMD-892 116 and other compounds (tacedinaline, [117][118][119] MLN4924, 120 piperlongumine, 121,122 prunetin 123 ) have also been under investigation for their antioxidant, anti-inflammatory, anti-ischemic, neuroprotective, and/or antitumour properties.…”
Section: Discussionmentioning
confidence: 99%
“…Primary hippocampal and cortical neurons from Tg2576 mice evidenced increased mitochondrial fission, decreased fusion and abnormal mitochondrial function [ 47 ]. Moreover, we previously demonstrated that prolonged AβO (1 μM, for up to 24 h) treatment caused mitochondrial fragmentation in mature primary hippocampal neurons [ 24 ] or in HT22 hippocampal cells without evidence of cell death [ 48 ]. Here, we evidence that short exposure to the same concentration of AβO is enough to induce a mild decrease in mitochondrial aspect ratio and an increase in mitochondrial circularity, supporting some degree of mitochondrial fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma cholesterol metabolite 27-hydroxycholesterol can induce an increase in HDAC activity, leading to aggravated synaptic damage in rats with Alzheimer’s disease (AD), resulting in impaired memory [ 103 ]. Moreover, HDAC also affects the crosstalk between endoplasmic reticulum-mitochondrial organelles in the hippocampus of AD mice and aggravates the microglial inflammatory response in the entorhinal cortex, causing cognitive impairment [ 104 , 105 ]. In addition, mice with conditional knockout of the HDAC9 gene from forebrain neurons reversed depressive disorders caused by chronic restraint stress [ 106 ].…”
Section: Role Of Chromatin Modifiers In Human Diseasesmentioning
confidence: 99%